Early Sensitivity to Morphology in Beginning Readers of Arabic - El Akiki, Carole; Content, Alain (Frontiers in Psychology, 2020)
The current study investigated the influence of morphological structure on the earliest stages of Arabic reading acquisition. More specifically, we aimed at examining the role of root and pattern units in beginners from Grade 1 to 3. A first set of reading tasks evaluated the presence of a morphology facilitation effect in word and pseudoword reading by manipulating independently the familiarity of roots and patterns. The second one pursued to examine the contribution of morphological awareness to reading performance. The results suggest that reading ability is early influenced by the awareness of morphological composition. Children read faster and more accurately pseudowords composed of familiar morphemes. Furthermore, regression analyses revealed, for every reading measure, a significant contribution of one morphological test in addition to grapheme knowledge. Results are discussed taking into account the differences obtained depending on lexicality and morpheme type (root or pattern).